2007
DOI: 10.1016/j.physletb.2007.06.067
|View full text |Cite
|
Sign up to set email alerts
|

The generalized second law of thermodynamics in the accelerating universe

Abstract: We show that in the accelerating universe the generalized second law of thermodynamics holds only in the case where the enveloping surface is the apparent horizon, but not in the case of the event horizon. The present analysis relies on the most recent SNe Ia events, being model independent.Our study might suggest that event horizon is not a physical boundary from the point of view of thermodynamics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 24 publications
2
101
0
Order By: Relevance
“…The generalized second law of thermodynamics is a universal principle governing the universe. Recently the generalized second law of thermodynamics in the accelerating universe enveloped by the apparent horizon has been studied extensively in [37,38,39]. For other gravity theories, the generalized second law has also been studied in [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The generalized second law of thermodynamics is a universal principle governing the universe. Recently the generalized second law of thermodynamics in the accelerating universe enveloped by the apparent horizon has been studied extensively in [37,38,39]. For other gravity theories, the generalized second law has also been studied in [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…It occurs not only in Einstein's gravity, but in other scenarios such as braneworld models [50][51][52][53], Horava-Lifshitz gravity [54], Lovelock gravity [47,55] and f (R) gravity [56]. Moreover, it has been shown that the obedience to the generalized second law of thermodynamics is fulfilled in the scenario of an accelerating expanding universe when one identifies the cosmological holographic boundary as the universe apparent horizon [57][58][59]. On the base of such facts, it can be argued that the apparent horizon must be considered as the physical horizon in dealing with thermodynamics issues, in the context of a universe with any curvature.…”
Section: Friedmann Equations From Thermodynamicsmentioning
confidence: 99%
“…According to the recent type Ia Supernovae data, it is suggested that in the accelerating universe the enveloping surface should be the apparent horizon rather than the event one from the thermodynamic point of view [37]. In flat FRW spacetime, the radius at the apparent horizon is given byr A = 1/H [38], and the dynamical apparent horizon is determined by the relation…”
Section: First Law Of Thermodynamicsmentioning
confidence: 99%